2003
DOI: 10.1891/vivi.2003.18.6.619
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Contribution of Experiencing and Witnessing Violence During Childhood on Child Abuse in the Parent Role

Abstract: This article examines adult respondents' abuse of children as a consequence of their own childhood experiences of abuse, both direct experiences of childhood violence (hitting) and exposure to interparental violence (witnessing). In particular, the study examines the extent to which these factors function interactively: Are both experience and exposure necessary or is either sufficient to increase disproportionately the probability of child abuse? Using data from the Second National Family Violence Survey, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…Having a personal history of maltreatment as a child has also been shown to be a risk factor for child maltreatment (Zuravin, McMillen, DePanfilis, & RisleyCurtiss, 1996;Cunningham, 2003;Goldman, Salus, Wolcott, & Kennedy, 2003;Narang & Contreras, 2005;Francis & Wolfe, 2008). Goldman and colleagues (2003), in a review of the literature, note that approximately one-third of caregivers who were victims of child maltreatment perpetuate the cycle of maltreatment on their own children.…”
Section: Generalmentioning
confidence: 99%
See 4 more Smart Citations
“…Having a personal history of maltreatment as a child has also been shown to be a risk factor for child maltreatment (Zuravin, McMillen, DePanfilis, & RisleyCurtiss, 1996;Cunningham, 2003;Goldman, Salus, Wolcott, & Kennedy, 2003;Narang & Contreras, 2005;Francis & Wolfe, 2008). Goldman and colleagues (2003), in a review of the literature, note that approximately one-third of caregivers who were victims of child maltreatment perpetuate the cycle of maltreatment on their own children.…”
Section: Generalmentioning
confidence: 99%
“…While history of maltreatment is examined here as a parental risk factor, note that it may also be considered a consequence or outcome of child maltreatment. Cunningham (2003) reported that caregivers who were hit when they were teens were 1.92 times more likely to admit to physically abusing their own children. When examining fathers, in particular, researchers found that physically abusive fathers were more likely to have experienced maltreatment as a child when compared to non-maltreating fathers (Francis & Wolfe, 2008).…”
Section: Generalmentioning
confidence: 99%
See 3 more Smart Citations